Superior calyceal access vs. other calyceal access in percutaneous nephrolithotomy: A systematic review and meta-analysis - Ma, Yucheng; Lin, Lede; Luo, Zhumei; Jin, Tao (Frontiers in Surgery, 2022)
Purpose: To evaluate the superior calyceal access's performance and safety in relation to other calyceal access during percutaneous nephrolithotomy (PCNL). Methods: The suggested reporting items for systematic reviews and meta-analysis were used to conduct this meta-analysis (PRISMA). To find pertinent studies for this meta-analysis, we searched Pubmed, Embase, Web of Science, and China National Knowledge Infrastructure (CNKI). Operation time and hospital stay are two secondary outcomes, whereas failed stone clearance and complication events are the two major outcomes. Utilizing Stata 15.0, RevMan 5.3, and R 4.0.2, relative data were extracted and evaluated. Results: This meta-analysis was based on 16 studies with 8541 individuals. Pooled results suggested that superior calyceal access could offer fewer failed stone clearance (OR: 0.64, 95%CI: 0.47-0.88, P=0.006) and lower additional puncture rate (OR:0.35, 95%CI:0.24-0.51, P<0.001) than other calyceal access. No complication difference was found (OR: 1.10, 95%CI: 0.78-1.56, P=0.57). Superior calyceal access could offer shorter operation time (SMD: -0.57, 95%CI: -0.98, -0.15, P=0.007). No hospital stay difference was found (SMD: 0.07, 95%CI: -0.09, 0.22, P=0.38). Large heterogeneity was detected in stone clearance comparison (I2=71%, P<0.001) and operation time (I2=97%, P<0.001). The stone clearance comparison also identified significant publication bias (P=0.026). These defects weaken the credibility of the results. Conclusion: Superior calyceal access in PCNL may result in a higher stone clearance rate, a lower rate of subsequent punctures, and a faster operation duration with no increase in postoperative complications or hospital stay for kidney stone patients, despite the significant heterogeneity and publication bias. By conducting bigger randomized controlled studies, this discovery still has to be confirmed.